Positive electrode slurry composition for lithium secondary battery, positive electrode comprising the same, and lithium secondary battery

CN116325208BActive Publication Date: 2026-10-27LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280006656.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-08
Filing Date
2022-07-07
Publication Date
2026-10-27
Estimated Expiration
2042-07-07

AI Technical Summary

Technical Problem

然而,当仅使用锂化羧甲基纤维素作为粘合剂时,因为在正极浆料的制备中触变性也是弱的,所以存在如下问题:当涂覆速率在正极活性材料层涂覆过程中变化时,因为所述涂覆速率不能适当地对应于正极组合物,所以不能均匀地形成正极活性材料层

Benefits of technology

[0028]因为根据本发明的正极浆料组合物具有能够灵活地响应涂覆过程期间变化的涂覆速率的流动性,所以能够通过使用该正极浆料组合物来制备正极,所述正极具有形成在正极集电器上的均匀的正极活性材料层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116325208B_ABST
    Figure CN116325208B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode slurry composition for a lithium secondary battery, and a positive electrode and a lithium secondary battery comprising the same, more specifically, when a method of manufacturing a positive electrode for a lithium secondary battery including a slurry coating process is used, by using a positive electrode slurry composition having thixotropy which can ensure flowability sufficient to flexibly respond to a change in slurry coating rate, the processability when manufacturing a positive electrode for a lithium secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Korean Patent Application No. 2021-0089726, filed on July 8, 2021, the entire contents of which are incorporated herein by reference.

[0002] This invention relates to a positive electrode slurry composition for lithium secondary batteries, as well as a positive electrode and a lithium secondary battery comprising the same. Background Technology

[0003] Recently, with the rapid development of electronic devices and electric vehicles, the demand for rechargeable batteries is increasing. In particular, with the trend towards miniaturization and lightweighting of portable electronic devices, the demand for rechargeable batteries with high energy density is increasing.

[0004] In secondary batteries, lithium-sulfur secondary batteries use sulfur compounds with sulfur-sulfur bonds as the positive electrode active material and substances such as alkali metals like lithium, or carbonaceous materials in which the insertion and extraction of metal ions such as lithium ions occur, or silicon or tin that form alloys with lithium. Specifically, lithium-sulfur secondary batteries store and generate electrical energy through a redox reaction in which, during discharge (as a reduction reaction), the sulfur-sulfur bond breaks while the oxidation number of sulfur decreases, and during charging (as an oxidation reaction), the sulfur-sulfur bond re-forms while the oxidation number of sulfur increases.

[0005] In particular, because sulfur, used as the positive electrode active material in lithium-sulfur secondary batteries, has a theoretical energy density of 1,675 mAh / g, which is about five times that of the positive electrode active materials used in conventional lithium secondary batteries, lithium-sulfur secondary batteries are capable of exhibiting high power and high energy density. Furthermore, sulfur is attracting attention as an energy source for medium to large-scale devices such as electric vehicles and portable electronic devices due to its advantages of low cost, abundant reserves, easy supply, and environmental friendliness.

[0006] Because sulfur has an electrical conductivity of 5 × 10⁻⁶ -30 S / cm is a non-conductive material, meaning that electrons generated by electrochemical reactions are difficult to move. Therefore, sulfur is combined with conductive materials such as carbon, which can provide sites for electrochemical reactions, and the resulting sulfur-carbon composite material is used.

[0007] To use sulfur-carbon composite materials as cathode materials, a common method for manufacturing cathodes is to prepare a slurry using sulfur-carbon composite materials, conductive materials, binders, and thickeners, and then coat the slurry onto the current collector.

[0008] However, conventional positive electrode slurries for lithium-sulfur secondary batteries have low thixotropy, making it difficult to ensure sufficient flowability when applied to solution coating processes. Therefore, dispersants and / or rheology modifiers that are friendly to sulfur-carbon composite materials as positive electrode active materials are used in the preparation of the positive electrode slurry. However, even with the use of these substances, the flowability is not significantly changed; instead, the charge / discharge performance is weakened by the use of dispersants and / or rheology modifiers.

[0009] On the other hand, the following research results have recently been published: the flowability of cathode slurry can be improved by using carboxymethyl cellulose-based materials as binders in the preparation of cathode compositions.

[0010] For example, in Korean Patent Publication No. 2016-0071740, carboxymethyl cellulose (CMC) is included as a binder in the preparation of the positive electrode composition to provide an aqueous positive electrode composition, thereby imparting stable and flexible electrode plate properties. However, when only carboxymethyl cellulose is used as a binder, the thixotropic slurry cannot be properly spread when the coating rate changes during the slurry coating process, resulting in the problem of uneven formation of the positive electrode active material layer.

[0011] Lei Qui et al. (Carbohydrate Polymers, Vol. 112, (2014), pp. 532-538) disclosed a positive electrode composition for lithium secondary batteries, which includes lithium-ionized carboxymethyl cellulose (LiCMC) as a binder. However, when using only lithium-ionized carboxymethyl cellulose as a binder, the thixotropy is also weak in the preparation of the positive electrode slurry, resulting in the following problem: when the coating rate varies during the coating process of the positive electrode active material layer, the coating rate cannot properly correspond to the positive electrode composition, thus preventing the uniform formation of the positive electrode active material layer.

[0012] Therefore, research is underway to improve the rheological properties of lithium-ion batteries, thereby enhancing the processability in the manufacture of positive electrodes for lithium-ion batteries and improving the charge / discharge performance of the manufactured batteries. However, currently developed positive electrode slurries have not shown significant effects on improving processability and battery performance when manufacturing positive electrodes for lithium-ion batteries.

[0013] [Existing technical documents]

[0014] [Patent Literature]

[0015] (Patent Document 1) Korean Patent Publication No. 2016-0071740

[0016] (Patent Document 2) Lei Qui et al. (Carbohydrate polymers, Vol. 112, (2014), pp. 532-538) Summary of the Invention

[0017] Technical issues

[0018] The inventors of this invention have conducted various studies to solve the above-mentioned problems, and have confirmed that if a positive electrode slurry composition for lithium secondary batteries is mixed with lithium-ion carboxymethyl cellulose (LiCMC) as a thickener and succinimide compounds as additives, the fluidity of the positive electrode slurry composition is improved. Therefore, even if the coating rate varies during the coating process of the positive electrode slurry composition during the production of the positive electrode, a positive electrode active material layer with good quality can be formed.

[0019] Therefore, one object of the present invention is to provide a positive electrode slurry composition for lithium secondary batteries, the slurry composition having excellent flowability and being able to flexibly respond to various process conditions during slurry coating.

[0020] Another object of the present invention is to provide a positive electrode and a method for manufacturing the same, wherein the positive electrode is prepared using the above-described positive electrode slurry composition with good flowability.

[0021] Another object of the present invention is to provide a lithium secondary battery comprising a positive electrode prepared using the above-described free-flowing positive electrode slurry composition.

[0022] Technical solution

[0023] To achieve the above objectives, the present invention provides a positive electrode slurry composition for lithium secondary batteries, the positive electrode slurry composition comprising a positive electrode active material, a conductive material, a binder, a thickener, an additive, and a solvent, wherein the thickener comprises lithium carboxymethyl cellulose (LiCMC), and the additive comprises a succinimide compound.

[0024] The present invention also provides a positive electrode for a lithium secondary battery, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on a surface of the positive electrode current collector, wherein the positive electrode active material layer is formed from the positive electrode slurry composition.

[0025] The present invention also provides a method for manufacturing a positive electrode for a lithium secondary battery, the method comprising the following steps: (S1) coating a positive electrode slurry composition onto a surface of a positive electrode current collector; (S2) drying the coating formed in step (S1); and (S3) rolling the coating to form a positive electrode active material layer.

[0026] The present invention also provides a lithium secondary battery, which includes the above-mentioned positive electrode, negative electrode, separator and electrolyte.

[0027] Beneficial effects

[0028] Because the cathode slurry composition according to the invention has a fluidity that allows it to flexibly respond to changes in the coating rate during the coating process, a cathode having a uniform layer of cathode active material formed on a cathode current collector can be prepared by using the cathode slurry composition.

[0029] Furthermore, lithium secondary batteries containing a positive electrode prepared using a positive electrode slurry composition with good flowability exhibit improved charge / discharge performance. Attached Figure Description

[0030] Figure 1 This is a graph showing the change of shear stress as a function of shear rate for the positive electrode slurry compositions of Example 1 and Comparative Example 1.

[0031] Figure 2 This is a graph showing the charge / discharge characteristics of the lithium-sulfur secondary batteries of Example 1 and Comparative Example 1. Detailed Implementation

[0032] The invention will be described in more detail below to aid in understanding it.

[0033] The terms and words used in this specification and claims should not be construed as limited to ordinary or dictionary terms, but rather as having meanings and concepts consistent with the technical concept of the invention, based on the principle that the inventor is able to properly define the concepts of the terms in order to describe his invention in the best possible way.

[0034] As used herein, the term "thixotropic" refers to the property that the viscosity increases when no shear stress is applied to the material, and decreases when shear stress is applied to the material.

[0035] As used herein, the term "solids" refers to the positive electrode active material, conductive material, binder, thickener, and additives in a positive electrode slurry composition for lithium secondary batteries, excluding solvents.

[0036] Positive electrode slurry composition for lithium secondary batteries

[0037] This invention relates to a positive electrode slurry composition having the following flowability: when manufacturing a positive electrode for a lithium secondary battery, it is sufficiently responsive to changes in the coating rate during the coating process used to form the positive electrode active material layer. Here, the term "response" means that when the coating rate increases, the viscosity of the positive electrode slurry composition decreases because the shear stress applied to the current collector and coating rod on which the coating material is coated increases, resulting in uniform coating at a fast coating rate; and when the coating rate decreases, the viscosity of the positive electrode slurry composition increases because the shear stress applied to the current collector and coating rod decreases, resulting in uniform coating at a slow coating rate.

[0038] The positive electrode slurry composition for lithium secondary batteries according to the present invention comprises a positive electrode active material, a conductive material, a binder, a thickener, an additive, and a solvent, wherein the thickener comprises lithium carboxymethyl cellulose (LiCMC), and the additive comprises a succinimide compound.

[0039] Because the positive electrode slurry composition for lithium secondary batteries contains succinimide compounds as additives, the slurry composition exhibits improved thixotropy and improved storage performance. With improved thixotropy, the ability to retain viscosity is enhanced even in the absence of shear stress during storage; therefore, the composition of the upper and lower portions of the slurry hardly changes over time, thus improving storage performance. If the composition of the upper and lower portions of the slurry changes, the internal composition of the slurry will differ during coating, potentially resulting in a coating with an uneven composition.

[0040] In the following sections, the present invention will be described in more detail, focusing on the individual components of the positive electrode slurry composition for lithium secondary batteries.

[0041] In this invention, the positive electrode active material may include at least one selected from the following: elemental sulfur (S8), Li2S n (n≥1, n is an integer), organic sulfur compounds and carbon-sulfur polymers [(C2S x ) n [2.5≤x≤50, n≥2, where x and n are integers]. Preferably, the positive electrode active material may contain elemental sulfur. For example, the positive electrode active material may be a sulfur / carbon composite material, and the sulfur / carbon composite material may be an S / CNT composite material obtained using sulfur (S) and carbon nanotubes (CNTs).

[0042] Furthermore, based on the total weight of the solids in the positive electrode slurry composition, the content of the positive electrode active material can range from 60% to 97% by weight. Specifically, the content of the positive electrode active material can be 60% or more, 70% or more, or 80% or more, and 91% or less, 93% or less, or 97% or less. If the content of the positive electrode active material is less than 60% by weight, the overall battery capacity may decrease. If the content of the positive electrode active material exceeds 97% by weight, the content of one or more of the conductive materials, binders, thickeners, and additives other than the positive electrode active material is relatively reduced, which may decrease the flowability, conductivity, or physical properties of the positive electrode slurry composition.

[0043] Furthermore, conductive materials are used to improve conductivity, and there are no particular limitations, as long as the conductive material is a conductive material that does not cause chemical changes in the lithium secondary battery.

[0044] Conductive materials may include at least one selected from the following: carbon black, graphite, carbon fiber, carbon nanotubes, metal powder, conductive metal oxide, and organic conductive materials. Carbon black may include at least one selected from the following: Ketjen black, SuperP, Danka black, acetylene black, and furnace black.

[0045] Based on the total weight of the solids in the positive electrode slurry composition, the content of conductive material can be from 0.01% to 30% by weight. Specifically, the content of conductive material can be 0.01% by weight or more, 2% by weight or more, or 4% by weight or more, and less than 10% by weight, less than 20% by weight, or less than 30% by weight. If the content of conductive material is less than 0.01% by weight, the conductivity of the positive electrode may decrease. If the content of conductive material exceeds 30% by weight, the flexibility of the positive electrode may decrease.

[0046] Furthermore, the adhesive holds the positive electrode active material within the positive electrode current collector and organically connects the positive electrode active materials to increase their bonding strength, and any adhesive known in the art can be used.

[0047] The adhesive can be a mixture or copolymer of two or more of the following substances: fluoropolymer adhesives, including polyvinylidene fluoride (PVdF) and / or polytetrafluoroethylene (PTFE); rubber adhesives, including at least one of styrene-butadiene rubber (SBR), nitrile rubber, and styrene-isoprene rubber; cellulose adhesives, including at least one of carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyol adhesives; polyolefin adhesives, including at least one of polyethylene and polypropylene; polyimide adhesives; polyester adhesives; acrylic adhesives, including acrylic monomers; and silane adhesives. According to one embodiment of the invention, the adhesive may preferably be a combination of rubber adhesives. Furthermore, considering compatibility with carboxymethyl cellulose thickeners, the adhesive may include SBR and / or acrylic adhesives.

[0048] Furthermore, the adhesive can be an emulsion-type adhesive. Typically, the adhesive for the cathode can be in the form of a linear polymer, as long as it enables the components in the cathode to bind together, and there are no particular limitations. However, if an emulsion-type adhesive is used, the components for the cathode can be combined most effectively in a point-to-point manner, and the bond strength is also good. In addition, using an emulsion-type adhesive, compared to a linear polymer-type adhesive, increases the solids content in the slurry.

[0049] Furthermore, based on the total weight of the solids in the positive electrode slurry composition, the binder content can range from 0.01% to 30% by weight. Specifically, the binder content can be 0.01% or more, 1% or more, or 2% or more, and less than 10% by weight, less than 20% by weight, or less than 30% by weight. If the binder content is less than 0.01% by weight, the physical properties of the positive electrode, such as bond strength, may deteriorate, thereby potentially leading to the removal of both the positive electrode active material and the conductive material. If the binder content exceeds 30% by weight, the ratio of positive electrode active material to conductive material decreases relatively, thereby potentially reducing the battery capacity.

[0050] In addition, thickeners can ensure the stability of the cathode slurry composition by imparting an appropriate viscosity to the cathode slurry composition, and can improve surface defects by reducing the re-aggregation of solids when the cathode slurry composition is coated onto the cathode current collector.

[0051] Thickeners may contain lithium-ionized carboxymethyl cellulose (LiCMC). This LiCMC can be represented by the following chemical formula:

[0052] <Chemical Formula 1>

[0053]

[0054] Wherein, R is H or CH2COOH, and n is 25 to 2000.

[0055] LiCMC is obtained by replacing the metal ions in conventional CMC with Li. The metal ions contained in conventional CMC can act as impurities inside the battery, thereby degrading the battery's performance. LiCMC, on the other hand, eliminates these impurities and contains lithium ions, thus minimizing the performance degradation caused by impurities.

[0056] Furthermore, the use of LiCMC with succinimide compounds can alter the internal interactions (hydrogen bonds) of the slurry, thereby improving its thixotropy corresponding to shear stress. Specifically, the thixotropy of the slurry may increase due to the hydrogen bond interactions between the functional groups (-OCH2COO- or -OR) of LiCMC and the internal functional groups (N-hydroxyl and carbonyl) of the succinimide compounds, thus improving the slurry's storage properties.

[0057] Furthermore, based on the total weight of the solids in the positive electrode slurry composition, the content of the thickener can be from 0.5% to 5% by weight. Specifically, the content of the thickener can be more than 0.5% by weight, more than 0.8% by weight, or more than 1% by weight, and less than 2% by weight, less than 3% by weight, or less than 5% by weight. If the content of the thickener is less than 0.5% by weight, the positive electrode slurry composition cannot be coated onto the positive electrode current collector because of its low viscosity and water-like flow. If the content of the thickener exceeds 5% by weight, a uniform coating may be difficult to form because of the high viscosity and hardness of the positive electrode slurry composition.

[0058] There are no particular limitations on the viscosity of the cathode slurry composition, and the viscosity can vary depending on the content of the thickener. However, considering the phase stability of the cathode slurry composition and the ease of the coating process, the viscosity at 25°C can be at least 1000 cP or at least 4500 cP.

[0059] In addition, additives can enable thixotropy to respond to changes in the coating rate during the coating process of coating the cathode slurry composition onto the cathode current collector during cathode production.

[0060] The additive contains succinimide compounds, and the succinimide compounds may include at least one selected from the following: N-hydroxysuccinimide (NHS), N-(2-hydroxyethyl)succinimide, N-succinimide acetate, N-succinimide methacrylate, N-succinimide acrylate, succinimide, and ethosuximide.

[0061] If succinimide compounds are included as additives, the solids content in the slurry increases, making it easier to control thixotropy. For example, when preparing a slurry, if succinimide compounds are used as additives in addition to the existing components, the effect of increasing solids is good, so the thixotropy of the slurry can be easily controlled.

[0062] Furthermore, based on the total weight of the solids in the cathode slurry composition, the additive content can range from 0.01 wt% to 5 wt%. Specifically, the additive content can be 0.01 wt% or more, 0.1 wt% or more, or 0.3 wt% or more, and less than 1.5 wt%, 3 wt% or less, or 5 wt% or less. If the additive content is less than 0.01 wt%, the thixotropic properties of the cathode slurry composition are poor, so it may be difficult to form a coating of uniform thickness when the coating rate varies during coating. If the additive content exceeds 5 wt%, the content of the LiCMC thickener is relatively reduced, and the stability of the cathode slurry composition is poor, which may lead to cracking after the coating is formed.

[0063] Furthermore, solvents can be used without particular restrictions, as long as the solvent can be mixed with the above-mentioned positive electrode active material, conductive material, binder, thickener and additives to form a positive electrode slurry composition.

[0064] Solvents may include organic solvents and / or aqueous solvents. Organic solvents may include at least one selected from the following: N-methyl-2-pyrrolidone (NMP), methoxypropyl acetate, butyl acetate, glycolic acid, butyl ester, ethylene glycol butyl ether, methylalkyl polysiloxane, alkylbenzene, propylene glycol, xylene, ethylene glycol monophenyl ether, aralkyl-modified methylalkyl polysiloxane, polyether-modified dimethyl polysiloxane copolymer, polyether-modified dimethyl polysiloxane copolymer, polyacrylate, alkylbenzene, diisobutyl ketone, organically modified polysiloxane, butanol, isobutanol, modified polyacrylate, modified polyurethane, and polysiloxane-modified polymers. Aqueous solvents may include water.

[0065] Based on the total weight of the positive electrode slurry composition, the solvent content can be between 55% and 70% by weight. Specifically, the solvent content can be 55% by weight or more, or 57% by weight or more, and less than 65% by weight, 67% by weight or less, or 70% by weight or less. If the solvent content is less than 55% by weight, the concentration of the positive electrode slurry composition becomes too high and hard, making it difficult to uniformly coat the positive electrode slurry composition onto the positive electrode current collector. If the solvent content exceeds 70% by weight, the concentration of the positive electrode slurry composition becomes too low and it flows down, making it difficult to control the positive electrode slurry composition during coating, and a long drying time may be required after the coating is formed.

[0066] In this invention, the thixotropic index (T) of the positive electrode slurry composition can be from 0.1 to 0.4, and the thixotropic index is represented by the following mathematical formula 1:

[0067] <Mathematical Formula 1>

[0068] Thixotropic index (T) = (viscosity of the cathode slurry composition at 10 rpm) / (viscosity of the cathode slurry composition at 1 rpm).

[0069] Viscosity was measured at 25°C.

[0070] The positive electrode slurry composition exhibits thixotropy, which is the property of increasing viscosity when no shear stress is applied and decreasing viscosity when shear stress is applied.

[0071] Thixotropy is defined by applying shear stress at a shear rate proportional to the rotational speed when the cathode slurry composition is rotated, using the principle of applying shear stress according to a shear rate proportional to the rotational speed. The viscosity of the cathode slurry composition at 10 rpm is compared to the viscosity of the cathode slurry composition at 1 rpm, as shown in Equation 1 above. The shear rate is 0.29 / s at 1 rpm and 2.9 / s at 10 rpm.

[0072] If the thixotropic index (T) is less than 0.1, the effective coating rate is limited when the coating rate varies during the coating process of the positive electrode slurry composition onto the positive electrode current collector because the viscosity at high rotation speeds is very low compared to that at low rotation speeds. If the thixotropic index (T) exceeds 0.4, the viscosity does not change significantly even with variations in the coating rate, making it potentially difficult to respond to the slurry. Specifically, the thixotropic index (T) can be ≥0.1, ≥0.15, or ≥0.2, and ≤0.3, ≤0.35, or ≤0.4.

[0073] Method for preparing positive electrode slurry composition for lithium secondary batteries

[0074] The present invention also relates to a method for preparing a positive electrode slurry composition for lithium secondary batteries. The types and weights of materials used in the preparation of the positive electrode slurry composition are as described above.

[0075] The positive electrode slurry composition can be prepared by adding the positive electrode active material, conductive material, binder, thickener and additives as described above to a solvent and mixing them.

[0076] The mixing can be performed by grinding, but there are no particular limitations, as long as it is a mixing method used in the art to form a slurry. For example, the grinding can be bead milling, roller milling, ball milling, grinding, planetary milling, zeta milling, or screw mixing milling. Preferably, bead milling can be applied to ensure uniform mixing and dispersibility of the components contained in the positive electrode slurry composition.

[0077] Positive electrode for lithium secondary batteries

[0078] The present invention also provides a positive electrode for a lithium secondary battery, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on a surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a binder, a conductive material, a thickener, and additives.

[0079] In this invention, there are no particular limitations on the positive electrode current collector, as long as it is conductive without causing chemical changes in the battery and can be used electrochemically stably at the charging voltage of the positive electrode. For example, the positive electrode current collector can be at least one selected from copper, aluminum, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof. Stainless steel can be surface-treated with carbon, nickel, titanium, or silver.

[0080] Furthermore, the shape of the positive electrode current collector is not particularly limited and can be in the form of a film, sheet, foil, mesh, porous body, foam, or nonwoven fabric. If necessary, fine irregularities can be formed on the surface of the positive electrode current collector, which can help improve adhesion to the positive electrode active material layer. There are no particular limitations on the method of forming irregularities on the surface of the positive electrode current collector, and known methods such as mechanical polishing, electrolytic polishing, or chemical polishing can be applied.

[0081] Furthermore, there are no particular limitations on the thickness of the positive electrode current collector, and it can be set within an appropriate range taking into account the mechanical strength or productivity of the positive electrode, or the capacity of the battery. For example, the thickness of the positive electrode current collector can typically range from 3 μm to 500 μm.

[0082] In this invention, the positive electrode active material layer is formed from the positive electrode slurry composition as described above, and may contain positive electrode active material, binder, conductive material, thickener, and additives. The types and amounts of the positive electrode active material, binder, conductive material, thickener, and additives are as described above.

[0083] There are no particular limitations on the thickness of the positive electrode active material layer, and it can be set within an appropriate range taking into account the mechanical strength of the positive electrode, the loading capacity, or the capacity of the battery. For example, the thickness of the positive electrode active material layer can typically be from 30 μm to 300 μm.

[0084] Method for manufacturing positive electrodes for lithium secondary batteries

[0085] The present invention also relates to a method for manufacturing a positive electrode for a lithium secondary battery, the method comprising the following steps:

[0086] (S1) Coating the positive electrode slurry composition onto one surface of the positive electrode current collector;

[0087] (S2) Dry the coating formed in step (S1); and

[0088] (S3) Roll the coating to form a positive electrode active material layer.

[0089] In step (S1), a coating can be formed by applying the positive electrode slurry composition to one surface of the positive electrode current collector. The positive electrode current collector and the positive electrode slurry composition are the same as described above.

[0090] There are no particular limitations on the coating method, as long as the method is capable of coating the slurry. For example, the coating method may be selected from at least one of the following: roller-to-roll coating, spin coating, nozzle printing, inkjet printing, slot coating, and dip coating, with roller-to-roll coating being preferred.

[0091] During the coating process using the coating method described above, the coating rate can be variable. Depending on the coating conditions, the coating rate can be varied to establish optimized drying conditions. In the process of coating the positive electrode slurry composition onto the current collector and drying the slurry composition, the coating rate is variable because the drying rate of the solvent varies depending on the properties of the positive electrode slurry composition.

[0092] In step (S2), the coating formed in step (S1) can be dried.

[0093] Through drying, the solvent contained in the positive electrode slurry composition may evaporate to form a layered coating.

[0094] The drying temperature can be above 30℃, above 40℃, or above 45℃, and below 60℃, below 70℃, or below 80℃, so as to form a high-quality positive electrode active material layer.

[0095] In step (S3), the coating formed in step (S2) can be rolled to form a positive electrode active material layer.

[0096] As a rolling process, a rolling process commonly used in the art can be introduced, and a rolling press can be used for rolling. For example, rolling using a rolling press can be performed as follows: with two rollers placed on the top and bottom of a positive current collector on which a coating is formed, pressure is applied to the positive current collector on which the coating is formed by the rollers, while the positive current collector on which the coating is formed is moved horizontally at the same time.

[0097] Lithium secondary batteries

[0098] The present invention further relates to a lithium secondary battery, which comprises a positive electrode, a negative electrode, a separator and an electrolyte.

[0099] In the lithium secondary battery according to the present invention, the structure, constituent materials and manufacturing method of the positive electrode are as described above.

[0100] In the lithium secondary battery according to the present invention, the negative electrode may include a negative electrode current collector, and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode active material layer (for example, a lithium foil) may be used alone.

[0101] The negative electrode current collector is not particularly limited, as long as the negative electrode current collector has electrical conductivity and does not cause chemical changes in the relevant battery. For example, the following substances can be used as the negative electrode current collector: copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel subjected to surface treatment with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloys and the like. In addition, similar to the positive electrode current collector, the negative electrode current collector may be in various forms, for example, a film, a sheet, a foil, a mesh, a porous body, a foam, a non-woven fabric and the like having fine irregularities on the surface thereof.

[0102] In addition, the negative electrode active material may include, but is not limited to, at least one carbon-based material selected from crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low-crystalline soft carbon, carbon black, acetylene black, Ketjen black, Super-P, graphene and carbon fiber, a Si-based material, a metal composite oxide such as Li x Fe₂O₃ (0≤x≤1), Li x WO₂ (0≤x≤1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2 and 3 of the periodic table, halogens; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄, Bi₂O₅; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides and the like.

[0103] In addition, the negative electrode active material may be a substance as follows: a metal composite oxide such as Sn x Me 1-x Me' y O z(Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2 and 3 of the Periodic Table of the Elements, halogens; 0<x≤1; 1≤y≤3; 1≤z≤8); oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅, and carbon-based negative active materials such as crystalline carbon, amorphous carbon or carbon composite materials may be used alone or in a combination of two or more thereof.

[0104] In the lithium secondary battery according to the present invention, as the electrolytic solution, any electrolytic solution that is conventionally used for manufacturing lithium secondary batteries may be used.

[0105] Lithium salts that can be contained as an electrolyte in the electrolytic solution may be used without limitation as long as they are generally used in electrolytic solutions for lithium secondary batteries. For example, the anion of the lithium salt may be any one selected from the following: F - , Cl - , Br - , I - , NO₃ - , N(CN)₂ - , BF₄ - , ClO₄ - , PF₆ - , (CF₃)₂PF₄ - , (CF₃)₃PF₃ - , (CF₃)₄PF₂ - , (CF₃)₅PF - , (CF₃)₆P - , CF₃SO₃ - , CF₃CF₂SO₃ - , (CF₃SO₂)₂N - , (FSO₂)₂N - , CF₃CF₂(CF₃)₂CO - , (CF₃SO₂)₂CH - , (SF₅)₃C - , (CF₃SO₂)₃C - , CF₃(CF₂)₇SO₃ - , CF₃CO₂ - , CH₃CO₂ - , SCN - and (CF₃CF₂SO₂)₂N - . The lithium salt may be LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiC₂F₆NO₄S₂) and / or LiNO₃.

[0106] In the electrolyte used in this invention, any organic solvent contained in the electrolyte can be used without limitation, provided that the organic solvent is commonly used in electrolytes for lithium secondary batteries. According to one embodiment of the invention, the organic solvent can be a carbonate, ester, ether, ketone, alcohol, or aprotic solvent. Ether solvents are typically used.

[0107] Carbonate solvents can specifically include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.

[0108] Ester solvents can specifically include methyl acetate, ethyl acetate, n-propyl acetate, ethyl 1,1-dimethylacetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanoic acid lactone, valerate lactone, mevalonic acid lactone, caprolactone, etc.

[0109] Ether solvents can specifically include dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, polyethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, etc.

[0110] Ketone solvents can specifically include cyclohexanone, etc. Alcohol solvents can specifically include ethanol, isopropanol, etc.

[0111] Specifically, aprotic solvents may include the following substances: nitriles such as acetonitrile; amides such as dimethylformamide; dioxolane such as 1,3-dioxolane (DOL); or sulfolane.

[0112] Non-aqueous organic solvents can be used alone or as a mixture of multiple solvents. When multiple solvents are mixed and used, the mixing ratio can be appropriately adjusted according to the desired battery performance.

[0113] In the lithium secondary battery according to the present invention, the separator can be a conventional porous polymer membrane used as a separator in the art. For example, the separator can be a single-layer porous polymer membrane or a laminate thereof made of polyolefin polymers, such as polyethylene, polypropylene, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer, or the separator can be a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber, polyethylene terephthalate fiber, etc., but not limited thereto.

[0114] In the lithium secondary battery according to the invention, the shape of the battery is not particularly limited and can be, for example, rolled, stacked, stacked-folded (including stacked-Z-folded) or layered-stacked, preferably stacked-folded.

[0115] In addition, lithium secondary batteries are manufactured by stacking a negative electrode, a separator, and a positive electrode in sequence, injecting an electrolyte to prepare an electrode assembly, placing the electrode assembly into a battery case, and then sealing and assembling the battery case with a cover plate and a gasket.

[0116] In this context, lithium secondary batteries can be classified into various battery types based on the materials used for the positive / negative electrodes, such as lithium-sulfur secondary batteries, lithium-air batteries, lithium-oxide batteries, and lithium all-solid-state batteries; based on their shape, they can be classified as cylindrical, rectangular, coin-shaped, and pouch-shaped; and based on their size, they can be classified as block-shaped and thin-film-shaped. The structures and fabrication methods of these batteries are known in the art, and their detailed descriptions are therefore omitted.

[0117] In this invention, the lithium secondary battery can be a lithium-sulfur secondary battery using a positive electrode material comprising a sulfur-carbon composite material as the positive electrode. The lithium-sulfur secondary battery can use lithium metal as the negative electrode active material. During the discharge of the lithium-sulfur secondary battery, an oxidation reaction of lithium occurs at the negative electrode, and a reduction reaction of sulfur occurs at the positive electrode. At this time, the reduced sulfur combines with lithium ions removed from the negative electrode, thereby converting into lithium polysulfides, and finally accompanied by a reaction forming lithium sulfide.

[0118] Furthermore, the present invention relates to a battery module comprising a lithium secondary battery, which can be used as a power source for devices requiring high capacity and high rate characteristics. Specific examples of such devices may include, but are not limited to: power tools driven by a battery-powered motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (Escooters); electric golf carts; and energy storage systems.

[0119] Preferred implementation scheme

[0120] In the following description, preferred embodiments of the invention will be presented to aid in understanding the invention. However, it will be apparent to those skilled in the art that the following examples are illustrative of the invention, and that various changes and variations are possible within the scope and spirit of the invention, and that such changes and variations are natural within the scope of the appended claims.

[0121] Example 1

[0122] (1) Preparation of positive electrode slurry composition

[0123] The positive electrode active material, conductive material, binder, thickener, and additives were mixed in a weight ratio of 92:5:2:0.7:0.3 to obtain a mixture. The positive electrode active material was an S / CNT composite material obtained by mixing sulfur (S, manufactured by Sigma-Aldrich) with carbon nanotubes (CNTs) using a ball mill and then heat-treating at 155°C. The conductive material was Danka Black, the binder was styrene-butadiene rubber (SBR), the thickener was LiCMC (LiCMC1000, GLchem), and the additive was hydroxysuccinimide (NHS).

[0124] The above mixture is mixed with water to prepare a positive electrode slurry composition.

[0125] (2) Manufacturing of the positive electrode

[0126] The positive electrode slurry composition is coated on one surface of an aluminum foil (Al foil) positive electrode current collector with a thickness of 12 μm, and then dried at 50°C for 2 hours and rolled to form a positive electrode with a positive electrode active material layer.

[0127] (3) Manufacturing of lithium-sulfur secondary batteries

[0128] A porous polyethylene separator with a thickness of 20 μm and a porosity of 45% is placed between the positive electrode and the lithium negative electrode, and then they are placed inside the casing. Electrolyte is then injected into the casing to manufacture a lithium-sulfur secondary battery in the form of a CR-2032 coin cell.

[0129] The electrolyte was obtained by adding 0.38 M LiTFSI and 0.31 M LiNO3 to a mixed solvent of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) (1:1, volume / volume).

[0130] Comparative Example 1

[0131] Except that no additives are used and the positive electrode active material, conductive material, binder and thickener are mixed in a weight ratio of 92:5:2:1, the positive electrode slurry composition, positive electrode and lithium-sulfur secondary battery are prepared in the same manner as in Example 1.

[0132] Experimental Example 1: Measurement of viscosity, thixotropic index and rheological properties of positive electrode slurry composition

[0133] For the positive electrode slurry compositions prepared in the examples and comparative examples, the viscosity was measured, the thixotropic index was calculated from the measured viscosity, and the rheological properties were measured. The results are shown in Table 1 below. Figure 1 middle.

[0134] The methods for measuring viscosity, calculating the thixotropic index, and measuring rheological properties are described below.

[0135] (1) Viscosity measurement

[0136] Four ml of the positive electrode slurry composition was placed in a container at 25°C, and the SCP-16 rotor (Brookfield Corporation) was installed in the container. The SCP-16 rotor was then rotated at speeds from 1 rpm to 10 rpm, and the viscosity (cP) measured at each speed was recorded. A viscometer (DV2T, Brookfield Corporation) was used for measuring the viscosity.

[0137] (2) Calculation of thixotropic index

[0138] Calculate the thixotropic index of the positive electrode slurry composition using the following mathematical formula 1:

[0139] <Mathematical Formula 1>

[0140] Thixotropic index (T) = (viscosity of the cathode slurry composition at 10 rpm) / (viscosity of the cathode slurry composition at 1 rpm).

[0141] The viscosity was measured at 25°C.

[0142] (3) Measurement of rheological properties

[0143] 1 g of the positive electrode slurry composition was placed in a rheometer (DHR-1, TA Instruments) and the shear stress (Pa) corresponding to the shear rate varying in the range of 0.1 / s to 50 / s was measured.

[0144] Table 1:

[0145]

[0146] As shown in Table 1, it can be seen that Example 1 is a positive electrode slurry composition containing an appropriate amount of NHS as an additive, which has high viscosity and a low thixotropic index value compared with Comparative Example 1, thereby exhibiting high thixotropic properties.

[0147] Furthermore, it can be seen that Comparative Example 1 is a positive electrode slurry composition without additives, and Comparative Example 1 has the viscosity required to form a slurry, but has a low response to changes in shear stress.

[0148] Figure 1 This is a graph showing the change of shear stress as a function of shear rate for the positive electrode slurry compositions of Example 1 and Comparative Example 1.

[0149] Reference Figure 1 It can be confirmed that the internal area of ​​the hysteresis loop is different, and it can be seen that the slurry of Example 1 has excellent thixotropic properties.

[0150] Experiment Example 2: Evaluation of Charge / Discharge Characteristics

[0151] The lithium-sulfur secondary batteries in the form of CR-2032 coin cells prepared in the examples and comparative examples were subjected to 0.1C charge / 0.1C discharge three times and 0.3C charge / 0.5C discharge three times within a voltage range of 1.8V to 2.5V to evaluate their charge / discharge characteristics.

[0152] Figure 2 This is a graph showing the charge / discharge characteristics of the lithium-sulfur secondary batteries of Example 1 and Comparative Example 1.

[0153] Reference Figure 2 The lithium-sulfur battery of Example 1 exhibited an initial discharge capacity of 1105 mAh / g, which is higher than the discharge capacity of 1080 mAh / g of Comparative Example 1, and demonstrated a lifespan performance of maintaining a discharge capacity of over 800 mAh / g for more than 100 cycles. This is equivalent to or better than the discharge capacity retention performance of the lithium-sulfur battery of Comparative Example 1 without additives.

[0154] Although the invention has been described above by way of limited embodiments and drawings, the invention is not limited thereto, and it will be apparent to those skilled in the art that various variations and modifications can be made within the scope equivalent to the technical spirit of the invention and the appended claims.

Claims

1. A positive electrode slurry composition for lithium secondary batteries, said positive electrode slurry composition comprising a positive electrode active material, a conductive material, a binder, a thickener, additives, and a solvent. in, The thickener comprises lithium-ionized carboxymethyl cellulose, and The additive contains succinimide compounds. The succinimide compounds include at least one selected from the following: N-hydroxysuccinimide, N-(2-hydroxyethyl)succinimide, N-succinimide acetate, N-succinimide methacrylate, N-succinimide acrylate, succinimide, and ethosuximide. Based on the total weight of solids in the positive electrode slurry composition, the content of the thickener is from 0.5% to 5% by weight. Based on the total weight of the solids in the cathode slurry composition, the content of the additive is from 0.01% to 5% by weight. The positive electrode active material includes at least one selected from the following: elemental sulfur; Li2S n Where n≥1, and n is an integer; organic sulfur compounds and carbon-sulfur polymers (C2S x ) n , where 2.5 < x ≤ 50, n ≥ 2, and x and n are integers.

2. The positive electrode slurry composition for lithium secondary batteries according to claim 1, wherein, The solvent includes at least one selected from organic solvents and aqueous solvents. The organic solvent comprises at least one selected from the following: N-methyl-2-pyrrolidone, methoxypropyl acetate, butyl acetate, glycolic acid, butyl ester, ethylene glycol butyl ether, methylalkyl polysiloxane, alkylbenzene, propylene glycol, xylene, ethylene glycol monophenyl ether, aralkyl-modified methylalkyl polysiloxane, polyether-modified dimethyl polysiloxane copolymer, polyacrylate, diisobutyl ketone, organically modified polysiloxane, butanol, isobutanol, modified polyacrylate, modified polyurethane, and polysiloxane-modified polymers. The aqueous solvent includes water.

3. A positive electrode for a lithium secondary battery, the positive electrode comprising: Positive current collector; and A layer of positive electrode active material is formed on one surface of the positive electrode current collector. in, The positive electrode active material layer is formed from the positive electrode slurry composition according to claim 1.

4. A method for manufacturing a positive electrode for a lithium secondary battery, the method comprising the following steps: (S1) Coating the positive electrode slurry composition of claim 1 onto one surface of the positive electrode current collector; (S2) Dry the coating formed in step (S1); and (S3) Roll the coating to form a positive electrode active material layer.

5. The method for manufacturing a positive electrode for a lithium secondary battery according to claim 4, wherein, The coating method is selected from at least one of the following: bar coating, roller-to-roll coating, spin coating, nozzle printing, inkjet printing, slot coating, and dip coating.

6. A lithium secondary battery, the lithium secondary battery comprising: The positive electrode as described in claim 3, negative electrode, Diaphragm, and Electrolyte.

7. The lithium secondary battery according to claim 6, wherein, The lithium secondary battery is a lithium-sulfur secondary battery.

Citation Information

Patent Citations

  • Lithium battery anode slurry additive, slurry, battery and preparation method

    CN102044675A

  • Nonaqueous lithium storage element

    EP3392891A1

  • Lithium secondary battery

    EP3706225A2

  • Positive material for lithium secondary battery, positive electrode for the same, and lithium secondary battery

    JP2001319657A

  • Non-aqueous electrolyte cell electrode binder, non-aqueous electrolyte cell electrode binder solution, non-aqueous electrolyte cell electrode slurry, non-aqueous electrolyte cell electrode, and non-aqueous electrolyte cell

    WO2020145295A1